Effects of management and natural disturbance on oribatid mites in montane forest - Farská, Jitka (Jihočeská univerzita, 2015)
The thesis studied effects of forest management and natural disturbance on oribatid mites in montane forests in South Bohemia (Czech Republic). We focused on the influence of (1) spruce monoculture establishment on the former beech forest, (2) management intensification in spruce forest and (3) forest dieback after bark-beetle outbreak. The impacts were pronounced especially like changes in species composition and distribution of functional traits.
Effects of management and natural disturbance on oribatid mites in montane forest
Keywords: pancířníci; Oribatida; hospodaření; les; smrk; Šumava; Oribatid mites; spruce; forest; management